Access to information as the first step in the investment stages for the effective reduction of energy consumption - Ducón-Sosa, Vladimir Camilo
Today, the world and Colombia are facing one of the most visible and impacting crisis due to the temperature rising. This crisis is making question us, how we are going to make it the next 50 years. Well, some symptoms are notorious, from the environment perspective. Climate change is a fact that we are going to live whit and is not going to disappear any time soon. The rising temperature of the earth is going to bring a numerous inconvenient. Some of them have shown since some years ago. The rapidly change of the temperature is bringing severe droughts, floods, electric storms, tornados, erode soils, hurricanes, extreme heat, wildfires, and another sort of natural disasters. These situations are produced by unbalance in the earth energetic equilibrium. This unbalance is undoubtedly produced by human action because of the accelerated human economy activities. So, we are trying to understand the general framework of the causes and possible solutions for human live in the earth for the next 100, 50 or 20 years. How can we, as main cause of the habitat damage, could mitigate some of these important and relevant problems that we create and jeopardize or survival in the planet earth. This document provides information specifically about the supply chain of electric power and water. Trying to describe it from general or global perspective to a local or regional one. We are going to foster the recognition of how these relevant resources are been provided and how the whole process can contribute to the emission of greenhouse gases or impact the sustainability of the communities. This document is also going to emphasize how important is to recognize and understand the problem from different perspectives to start to suggest solutions using 4.0 technologies as efficient tools to start to take action to mitigate some of the causes at local context. The potential of optimize the use resources and reduce.